DETECTION Escherichia coli IN DRINKING WATER SOURCES IN CHICKEN FARMING IN NARMADA DISTRICT, LOMBOK BARAT REGENCY - novarina sulsia ista'in ningtyas; alfiana laili dwi agustin; septyana eka rahmawati (Jurnal Biosains Pascasarjana, 2022)
Water plays an important role in human life. One of the sources of water used by the community is a source of water that comes from wells. The water source in the poultry area in Narmada is not only used for livestock needs but is utilized and consumed by the community especially farmers around the water source. The distance between the water source and the poultry area is less then 15 meters which is the cause of contamination. Research the aimed to detect contaminating bacterial in water source in Poultry of Narmada Regency. The study used a survey method with cross sectional study approach which was carried out in September 2022. Sample were taken using sterile bottles which were then cultured in EMBA, NA and biochemical test. The result of this study showed that there were four samples contaminated with E.coli which was marked with a metallic green on EMBA and the show basil and red colors under microscope.